Site specific PEGylation of β-lactoglobulin at glutamine residues and its influence on conformation and antigenicity. (September 2019) - Luo, Shunjing; Lu, Xuli; Liu, Chengmei; Zhong, Junzhen; Zhou, Lei; Chen, Tingting
Abstract: β-lactoglobulin (β-LG) is one of the main allergens in milk. Polyethylene glycol (PEG) modification (PEGylation) was found to have the ability to reduce the antigenicity of proteins. To determine the effect of site specific PEGylation on β-LG antigenicity and conformation, we applied 5 kDa methoxy polyethylene glycol-amine (mPEG-NH2 ) to modify β-LG at glutamine (Gln) residues under the catalysis of transglutaminase. The antigenicity of β-LG was measured using rabbit IgG antibodies by indirect competitive ELISA. The result indicated that the antigenicity of β-LG was decreased from 72.2 μg/mL to 22.7 μg/mL after PEGylation. SDS-PAGE and MALDI-TOF-MS showed that the molecular mass of native β-LG was about 18.3 kDa while the PEGylated β-LG had a molecular mass of 23.4 kDa, which meant that mono-PEGylated β-LG was obtained after PEGylation and purification by cation exchange chromatography. Additionally, the circular dichroism spectrum of the PEGylated β-LG was approximately superimposed on that of β-LG and the secondary structure content of β-LG also had no significant changes after PEGylation, which indicated that the secondary structure of β-LG was preserved. After PEGylation, the intrinsic fluorescence intensity of β-LG decreased from 6361 to 5159 while the surface hydrophobicity increased, which indicated that the tertiary structure of β-LG was slightly changed. PEGylation site analysis result showed that Gln 155 or Gln 159 might be the most possible binding site. In conclusion, the decrease of the antigenicity of β-LG induced by the PEGylation is mainly due to the steric shielding effect of PEG chain rather than conformational changes of β-LG. Graphical abstract: Unlabelled Image Highlights: Enzymatic PEGylation was first used to modify β-LG at Gln residues. MonoPEGylated β-LG was obtained by purification of cationic exchange chromatography. After PEGylation, the antigenicity of β-LG decreased remarkably. The enzymatic PEGylation had no significant effect on the conformation of β-LG. The decrease of antigenicity is mainly due to the steric shielding effect of PEG.